2013
DOI: 10.1111/jcmm.12129
|View full text |Cite
|
Sign up to set email alerts
|

A new gamboge derivative Compound 2 inhibits cancer stem‐like cells via suppressing EGFR tyrosine phosphorylation in head and neck squamous cell carcinoma

Abstract: Cancer stem-like cells represent a population of tumour-initiating cells that lead to the relapse and metastasis of cancer. Conventional anti-cancer therapeutic drugs are usually ineffective in eliminating the cancer stem-like cells. Therefore, new drugs or therapeutic methods effectively targeting cancer stem-like cells are in urgent need to successfully cure cancer. Gamboge is a natural anti-cancer medicine whose pharmacological effects are different from those of conventional chemotherapeutical drugs and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Treatment with cetuximab also promotes differentiation of CSCs and impairs resistance of CSC to chemo/radiation 161 . Also, a newly discovered gamboge derivative compound 2 showed effective inhibition of HNSCC by targeting a CSC population through EGFR tyrosine phosphorylation 162 . However, another study has demonstrated that the EGFR-targeted agents, such as cetuximab and erlotinib, show only modest effects on tumor control of HNSCC 161 …”
Section: Clinical and Therapeutic Implications Of Hnscc Cscsmentioning
confidence: 99%
“…Treatment with cetuximab also promotes differentiation of CSCs and impairs resistance of CSC to chemo/radiation 161 . Also, a newly discovered gamboge derivative compound 2 showed effective inhibition of HNSCC by targeting a CSC population through EGFR tyrosine phosphorylation 162 . However, another study has demonstrated that the EGFR-targeted agents, such as cetuximab and erlotinib, show only modest effects on tumor control of HNSCC 161 …”
Section: Clinical and Therapeutic Implications Of Hnscc Cscsmentioning
confidence: 99%
“…Interestingly, the Gamboge derivate Compound 2 (C2) is able to inhibit growth also in HNSCC stem cells. Indeed, it can inhibit formation of tumor spheres and repress the expression of multiples genes related to cancer stem cell phenotype by blocking the activation of EGFR pathways [132]. Since one of the main causes of failure in HNSCC treatment is the enrichment of CSCs population, which are resistant to current therapy, the future use of this molecule in combination with chemoradiotherapy could prevent the selective enrichment of CSCs after HNSCC conventional treatment.…”
Section: Therapeutic Activity Of Molecules Derived From Plantsmentioning
confidence: 99%